Nitrogen Sources Take Roles on Different Growth Balance of Red Beet (Beta vulgaris) - Mochammad Roviq; Ellis Nihayati; Sitawati Sitawati; Soemarno Soemarno (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2022)
One aim of productivity improvement on red beet was to restrain over-reducing the betacyanin as a secondary metabolite. Different nitrogen (N) sources were projected to affect growth, yield, and both primary and secondary plant metabolites. The research was carried out to find the effect of different sources and dosages of N on the production improvement and betacyanin. The N sources consisted of 5Ca(NO3)2NH4NO310H2O, NH4NO3NH4H2P04KCI, NO3H2P04KCI, CO(NH2)2, and (NH4)2SO4 with the N dosages of 75, 150, 225 kg N/ha and without N treatment as a control. The results showed that the enhancement of N dosages increased higher beet root fresh weight (BRFW) for about 42-50% than control. The 5Ca(NO3)2NH4NO310H2O and CO(NH2)2 increased BRFW and were higher than other N sources. The said N sources also contributed to 36% and 25% higher total betacyanin (BT) than those of (NH4)2SO4 and control, respectively. BRFW had the similar with BT, yet opposite patterns with betacyanin content (BC). The increase N dosages from any source diminish 20-33% BC, which was correlated with the increase of BRFW and BT following the sigmoidal pattern based on the logistics model during the growing period.